2021
DOI: 10.1109/tie.2020.3044776
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Model Predictive Control for Mobile Medical Robot Using Neural Optimization

Abstract: Mobile medical robots have been widely used in various structured scenarios, such as hospital drug delivery, public area disinfection, and medical examinations. Considering the challenge of environment modeling and controller design, how to achieve the information from the human demonstration in a structured environment directly arouse our interests. Learning skills is a powerful way that can reduce the complexity of algorithm in searching space. This is especially true when naturally acquiring new skills, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…[15]. Researchers have verified through experiments that closed-loop control may be more practical [31][32][33], as shown in Figure 2.…”
Section: Control Systemsmentioning
confidence: 87%
“…[15]. Researchers have verified through experiments that closed-loop control may be more practical [31][32][33], as shown in Figure 2.…”
Section: Control Systemsmentioning
confidence: 87%
“…Imitation learning (IL), also referred to as learning from demonstration (LfD), is a powerful approach for complex manipulation tasks, which perceives and reproduces human movements without the need of explicit programming of behavior ( Takamatsu et al, 2007 ; Kormushev et al, 2011 ; Suomalainen and Kyrki, 2017 ; Hu et al, 2020 ). Among the IL approaches, DMPs ( Ijspeert et al, 2013 ) have shown the ability to generalize demonstrations in different manipulation tasks ( Peters and Schaal, 2008 ; Metzen et al, 2014 ; Hu et al, 2018 ; Sutanto et al, 2018 ).…”
Section: Related Workmentioning
confidence: 99%
“…(2) How to devise the desired local filter in the presence of sensor energy-induced missing measurement phenomenon? (3) Based on the acquired local localization information, how to develop a feasible fusion localization scheme for the addressed RL? Here, we endeavour in handling the listed challenges and the advantages The rest of this paper is arranged as follows.…”
Section: Introductionmentioning
confidence: 99%